Pendidikan Interaksional dan Relevansinya dalam Pendidikan Islam - Machfudzil Asror (rogram Studi Pendidikan Agama Islam (PAI) Fakultas Tarbiyah Institut Agama Islam Tarbiyatut Tholabah (IAI TABAH) Lamongan, 2019)
Talking about the problem of education is very broad discussion, so the author focuses his research in the formulation of research problems. The formulations are (1) what is the concept of interactional education? (2) what is the concept of Islamic education according to Islamic education experts? (3) how is the relevance of interactional education in Islamic education? The objectives of this study are (1) to know the concept of interactional education (2) to find out the opinions of Islamic education experts on Islamic education (3) to find out the relevance of the concept of interactional education in Islamic education. This study uses a qualitative approach, one of the types of qualitative approaches is library research (library research) or also called non-reactive research. Then the way to collect various data and information will be done through a study of documentation, namely a review of references that relate to the focus of the research problem. The documents in question are primary (primary source) and secondary books (supporting sources) which discuss interactional education and social reconstruction curriculum as well as about Islamic education. From this study there are several research results, including: the relevance between interactional educational goals and the objectives of Islamic education, the relevance of interactional educational curricula with Islamic education curricula, the relevance of interactional educational material to Islamic education material, the relevance of interactional educational methods / strategies with the method of Islamic education, the relevance between the role of education teacher interactionally with the role of Islamic education teachers, the relevance between the position of students in interactional education with Islamic education students, and the relevance of evaluating interactional education with evaluating Islamic education and implementing interactional education in Islamic education in Indonesia.